THE USE OF EDUCATIONAL GAMES AS AN EVALUATION TOOL IN PRIMARY SCHOOL SCIENCE LEARNING - Sucilia Tri Lestari; Lailati Rohmah; Bianca Ayu Prastika (International Islamic Schools Alliance, 2025)
This study aims to analyze the use of educational games as an evaluation tool in science learning in elementary schools. The method used is a literature study with a qualitative approach, where data is obtained from various journals, articles, and relevant documents. The results showed that educational games such as Educandy, Wordwall, Kahoot, and Quizizz effectively increase student engagement, motivate learning, and support 21st century skills. Educational games make evaluation more engaging, provide instant feedback to teachers and help design optimal learning. Nonetheless, their implementation still faces challenges, such as lack of technological literacy, limited digital devices, and the need to adapt applications to the curriculum. This study concludes that educational games are effective and relevant evaluation media to support science learning in elementary schools. Further development is needed so that this technology can be optimally utilized in improving the quality of education in the digital era.